Motywacyjne i osobowościowe determinanty używania papierosów elektronicznych. Konstrukcja narzędzia pomiaru motywów wapowania - Niezabitowska, Agata
The construction of the Motives for Vaping and Smoking Scale (MVSS) began withan exploratory qualitative study (N=148 individuals), which led to the extraction of fifteenindependent motives for vaping. Among them, nine also referred to smoking (non-specificmotives), while six remained specific only to vaping (specific motives). After obtaining highcontent validity indicators for the preliminary classification of motives in a survey of competentjudges, I began validation studies in a sample of 1,217 smokers (including 588 vapers).I conducted a series of confirmatory factor analyses – separately for non-specific and specificmotives – to determine the theoretical validity of the tool. For non-specific motives, I obtainedan 8-factor solution and extracted the following motives: compulsion, habit, stimulation,pleasure, tension reduction, social liberation, conformity, and smoking/puffing. For specificvaping motives, I obtained a 4-factor solution and extracted the following motives:substitution/health issues, freedom of use/smell, economic issues, and taste and smell issues.I determined criterion validity by correlating the motives for vaping with the severity of nicotinedependence (convergent validity) and with self-control (discriminant validity). Reliabilitywas examined by analyzing the Cronbach's α and McDonald's ω internal consistency, the itemtotal correlation, and the test-retest coefficients (on a separate sample N=10). The scale obtainedgood indicators of criterion validity and reliability. There were significant differencesin motives, measured by the MVSS, related to sex, age, and the type of cigarettes used.The study of personality determinants of vaping motivation was conducted on a sampleof 248 e-cigarette users. First, the correlations of personality traits of the HEXACO model9with vaping motives, measured by MVSS, were examined. The results showed that vapingmotives were negatively associated primarily with the trait of honesty-humility. The higherthe level of this trait, the weaker were these motives. Compared to the results of studieson conventional cigarettes (Dash et al., 2021; Hakulinen et al., 2015; Munafo et al., 2007),extraversion was not correlated with vaping motives. Emotionality correlated positivelywith motives of pleasure, tension reduction and conformity. Secondly, I defined the differencesin the intensity of vaping motivation and nicotine dependence between individuals with specificpersonality profiles. Five personality profiles were identified, among which one with highconscientiousness and high honesty-humility, could be considered "protective," not conduciveto vaping. In contrast, the other, with high emotionality and low extraversion and agreeableness,represented a risk profile for increased vaping. Significant differences were found betweensubjects with specific personality profiles in the intensity of five vaping motives, includingthe three specific motives: freedom of use/smell, economic issues, and taste/smell issues.There were no significant differences in the severity of nicotine dependence. The last aimof the study was to determine the mediating role of vaping motives in the relationship betweenpersonality traits and the severity of nicotine dependence. An indirect effect occurred,as hypothesized, in all the relationships analyzed. Tension reduction mediated the relationshipbetween emotionality and nicotine addiction, stimulation interacted between extraversionand addiction, and habit mediated the relationship between low conscientiousness and nicotineaddiction.To sum up, validated the Motives for Vaping and Smoking Scale is a valid and reliabletool and can be used both in further quantitative research on the vaping phenomenonand in clinical practice.
Keywords: electronic cigarettes; vaping; vaping motives; personality traits